Tilt Angle and Inverter Input Voltage Optimization for Rooftop Photovoltaic Systems using Whale Optimization - Mulyana Mulyana; Muhamad Haddin (Institut Teknologi Dirgantara Adisutjipto, 2026)
Optimizing the performance of rooftop photovoltaic (RTPV) systems is crucial maximize energy production, especially in limited urban spaces. The main problem with the 122,040 Wp RTPV system is a significant performance gap, where the peak output power only reaches 95.93 kW, suggesting that the operational configuration may not be at the optimal point. The novelty of this research lies in the simultaneous optimization of two critical parameters: the geometric tilt angle (β) and the electrical inverter input voltage (VDC), a dual-parameter approach that contrasts with prior studies focusing on single-parameter optimization. This study aims to determine the optimal power output by employing the Whale Optimization Algorithm (WOA). The WOA method was selected for its superior ability to navigate complex search spaces by mimicking the bubble-net hunting strategy of humpback whales through a spiral model and a shrinking encircling mechanism to identify the global optimum. Simulation results show that convergence is achieved at the 75th iteration. The optimization results demonstrate a significant performance improvement, increasing the output power from 95.93 kW to 105.01 kW, which represents a 9.46% efficiency gain. This simultaneous optimization, resulting in a panel β of 26.26° and VDC of 629.66 V, proves to be a robust technical contribution for shifting the operating point toward the global maximum power point (GMPP) in industrial-scale RTPV systems.